2008
DOI: 10.1002/jnr.21897
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular glutathione mediates the denitrosylation of protein nitrosothiols in the rat spinal cord

Abstract: Protein S-nitrosothiols (PrSNOs) have been implicated in the pathophysiology of neuroinflammatory and neurodegenerative disorders. Although the metabolically instability of PrSNOs is well known, there is little understanding of the factors involved in the cleavage of S-NO linkage in intact cells. To address this issue, we conducted chase experiments in spinal cord slices incubated with S-nitrosoglutathione (GSNO). The results show that removal of GSNO leads to a rapid disappearance of PrSNOs (t1/2 ~ 2h), which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(42 citation statements)
references
References 45 publications
2
40
0
Order By: Relevance
“…In the case of the protein-SNO reaction with GSH, two different outcomes are depicted, namely denitrosylation or S-glutathionylation. Both types of reactions have been reported (153,190) and further study is necessary to understand the molecular basis for why one or the other reaction is favored with particular proteins and conditions (64). Glutaredoxin and thioredoxin function to repair the oxidized sulfyhydryls and prevent irreversible modification, aggregation, and degradation.…”
Section: B Glutaredoxin and Neurodegenerationmentioning
confidence: 99%
“…In the case of the protein-SNO reaction with GSH, two different outcomes are depicted, namely denitrosylation or S-glutathionylation. Both types of reactions have been reported (153,190) and further study is necessary to understand the molecular basis for why one or the other reaction is favored with particular proteins and conditions (64). Glutaredoxin and thioredoxin function to repair the oxidized sulfyhydryls and prevent irreversible modification, aggregation, and degradation.…”
Section: B Glutaredoxin and Neurodegenerationmentioning
confidence: 99%
“…In cultured cells, exposure to authentic NO, nitric oxide donors, or other RNS was found to inhibit GAPDH activity (75,218,266). The mechanisms of inhibition somewhat differ depending on the type of RNS used in experimental settings.…”
Section: Glycolysismentioning
confidence: 99%
“…These effects are likely mediated by the nitrosative changes in microtubules and microtubuleassociated proteins, such as nitration of a-tubulin and tau (43,44,79). Furthermore, a-and b-tubulins are robustly and persistently S-nitrosylated in vitro and in vivo (20,218). However, the functional significance of S-nitrosylation of cytoskeletal proteins has not been thoroughly tested.…”
Section: Defects In Axonal and Dendritic Transportmentioning
confidence: 99%
“…The latter constitutes a system together with GSH that governs the reversible S-nitrosylation of multiple SNO proteins, including G-protein receptor kinase, ␤-arrestin, and NF-B ). In vitro experiments with spinal cord slices revealed that SNO proteins are primarily denitrosylated via rapid transnitrosylation with GSH, suggesting that this system may be particularly important for SNO-mediated signaling in the nociceptive system (Romero and Bizzozero, 2009). …”
Section: Denitrosylation By Redoxinsmentioning
confidence: 99%